Evaluation of radio-morphometric indices of mandible using digital panoramic radiography: a radiographic study - Katru, Sreekar; Tumarada, Prasanth; Gummadi, Anusha; Kuraganti, Basavanthi; Panangipalli, Sai Sravya; Bytaru, Hari Shanmukha (International Journal of Dental Materials, 2023)
Background: Bone mineral density (BMD) varies with race, ethnicity, age, and gender. Thus arises the need for population-specific value ranges. Qualitative and quantitative indices of the mandible have also been used for panoramic radiographs to assess bone quality and to observe signs of resorption and osteoporosis.Aim: To measure the radio-morphometric indices in a digital panoramic radiograph and to find the inter-relationship of the indices with the age and sex of the patients. Materials and Methods: The study included 100 digital panoramic radiographic images of patients, and the samples were divided into four age groups. A panoramic radiograph of each patient was taken, and radio-morphometric indices were determined. Four indices, namely, cortical width at the gonion (GI) and below the mental foramen (MI), Mandibular cortical index (MCI) and Panoramic Mandibular Index (PMI), were measured bilaterally in all panoramic radiographs. All images were analyzed, and index values were calculated by applying linear measurements on the panoramic radiographs.Results: Statistically significant differences were observed among the study population.Conclusion: Radio-morphometric indices in a panoramic radiograph may possibly be used as a potential screening tool in identifying individuals with osteoporosis.